The Coexistence Relationship Between Plants and Soil Bacteria Based on Interdomain Ecological Network Analysis - Cong, Wei; Yu, Jingjing; Feng, Kai; Deng, Ye; Zhang, Yuguang (Frontiers in Microbiology, 2021)
The relationship between plants and their associated soil microbial communities plays a crucial role in maintaining ecosystem processes and function. However, identifying these complex relationships is challenging. In this study, we constructed an inter-domain ecology network (IDEN) of plant-bacteria based on SparCC pair-wise associations using synchronous aboveground plant surveys and belowground microbial 16S rRNA sequencing among four different natural forest types along the climate zones in China. The results found that a total of 48 plants were associated with soil bacteria among these four sites and soil microbial group associations with specific plant species was existed within the observed plant-bacteria coexistence network. Only 0.54% OTUs was shared by the four sites, and the proportion of unique OTUs for each site ranged from 43.08% to 72.28%, which occupied a large proportion of soil bacterial community composition.The plant-bacteria network had a distinct modular structure (P <0.001). The tree Acer tetramerum was identified as the network hubs in the warm temperate coniferous and broad-leaved mixed forests coexistence network, and indicates that it may play a key role in stabilizing of the community structure of these forest ecosystems. Therefore, IDEN of plant-bacteria provides a novel perspective for exploring the relationships of inter-domain species, and this study provides valuable insights into understanding coexistence between above-ground plants and below-ground microorganisms.